2018
DOI: 10.3892/ijo.2018.4345
|View full text |Cite
|
Sign up to set email alerts
|

S-phase kinase-associated protein 2 is involved in epithelial-mesenchymal transition in methotrexate-resistant osteosarcoma cells

Abstract: Osteosarcoma (OS), a common worldwide primary aggressive bone malignancy, arises from primitive transformed cells of mesenchymal origin and usually attacks adolescents and young adults. Methotrexate (MTX) is the anti-folate drug used as a pivotal chemotherapeutic agent in the treatment of OS. However, patients with OS often develop drug resistance, leading to poor treatment outcomes. In the present study, in order to explore the underlying mechanisms responsible for MTX resistance, we established MTX-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
1
21
0
1
Order By: Relevance
“…Alterations in the morphology of cells treated with vemurafenib for 5-7 days were reported for a panel of human melanoma cells, where the flattened shape of cells was further connected to senescent phenotype [32]. An increase in stress fiber numbers was noticed in melanoma cells resistant to vemurafenib by Misek et al [33], while a spindle-like or mesenchymal-like shape and elevated adhesion were reported in a number of studies on different cancer cells exhibiting drug resistance [34][35][36]. In addition to their altered shape, we also noticed that resistant lines showed a slightly lowered proliferation rate compared to parental ones.…”
Section: Discussionmentioning
confidence: 93%
“…Alterations in the morphology of cells treated with vemurafenib for 5-7 days were reported for a panel of human melanoma cells, where the flattened shape of cells was further connected to senescent phenotype [32]. An increase in stress fiber numbers was noticed in melanoma cells resistant to vemurafenib by Misek et al [33], while a spindle-like or mesenchymal-like shape and elevated adhesion were reported in a number of studies on different cancer cells exhibiting drug resistance [34][35][36]. In addition to their altered shape, we also noticed that resistant lines showed a slightly lowered proliferation rate compared to parental ones.…”
Section: Discussionmentioning
confidence: 93%
“…Not only that, SKP2 has also been reported to exert an effect in DNA damage response, DNA repair, tumor angiogenesis and drug resistance [40,41] . For example, Ding et al have demonstrated that SKP2 overexpression was also closely related to the acquisition of methotrexate-resistant and EMT properties in osteosarcoma [42] . Due to the extensive carcinogenic effects of SKP2, research on the anti-tumor activity of SKP2 small molecule inhibitors is in full swing.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted shRNA against SKP2 enhanced drug sensitivity in these cell lines. [394]. The novel Skp2 inhibitor, compound 25, was shown to have antitumour activities and to cooperate with chemotherapeutic agents to suppress cancer cell survival [393], making it of potential interest in osteosarcoma.…”
Section: Cancer Stem Cells and Tumour Microenvironmentmentioning
confidence: 99%